Empagliflozin Reverses Oxidized LDL-Induced RECK Suppression, Cardiotrophin-1 Expression, MMP Activation, and Human Aortic Smooth Muscle Cell Proliferation and Migration - Bysani Chandrasekar; Srinivas Mummidi; Vincent G. DeMarco; Yusuke Higashi (Mediators of Inflammation)
Persistent oxidative stress and inflammation contribute causally to smooth muscle cell (SMC) proliferation and migration, the characteristic features of vascular proliferative diseases. Oxidatively modified low-density lipoproteins (OxLDL) elevate oxidative stress levels, inflammatory responses, and matrix metallopeptidase (MMP) activation, resulting ultimately in SMC migration, proliferation, and phenotype change. Reversion-inducing cysteine-rich protein with Kazal motifs (RECK) is a membrane-anchored MMP inhibitor. Empagliflozin is an SGLT2 inhibitor and exerts pleiotropic cardiovascular protective effects, including antioxidant and anti-inflammatory effects. Here, we investigated (i) whether OxLDL regulates RECK expression, (ii) whether ectopic expression of RECK reverses OxLDL-induced SMC migration and proliferation, and (iii) whether pretreatment with empagliflozin reverses OxLDL-induced RECK suppression, MMP activation, and SMC migration, proliferation, and differentiation. Indeed, results show that OxLDL at pathophysiological concentration promotes SMC migration and proliferation via NF-κB/miR-30b-dependent RECK suppression. Moreover, OxLDL changed the SMC phenotype to a more pro-inflammatory type, and this effect is blunted by RECK overexpression. Further, treatment with empagliflozin reversed OxLDL-induced miR-30b induction, RECK suppression, MMP activation, SMC migration, proliferation, and proinflammatory phenotype changes. OxLDL-induced cardiotrophin (CT)-1 expression and CT-1 stimulated SMC proliferation and migration in part via leukemia inhibitory factor receptor (LIFR) and glycoprotein 130 (gp130). Ectopic expression of RECK inhibited these effects by physically associating with LIFR and gp130, as evidenced by immunoprecipitation/immunoblotting and double immunofluorescence. Importantly, empagliflozin inhibited CT-1-induced mitogenic and migratory effects. Together, these results suggest the therapeutic potential of sustaining RECK expression or empagliflozin in vascular diseases characterized by SMC proliferation and migration.